Women at work, 1860-1939 : how different industries shaped women's experiences - Hall, Valerie G. (Woodbridge, Suffolk : Boydell Press, 2013)
This book examines three different groups of women - in coal mining communities, in inshore fishing communities and in agricultural labour. It demonstrates how the work these groups undertook was fundamental in shaping their experiences as women in different ways and shows that women's experiences varied within class as well as between classes.
Part I. Women in Coal Mining Communities -- 1. 1860-1914: 'Stay at home and look after your husband' -- 2. The Inter-War Years: The Contrasting Roles of Mining Women -- Part II. Women in Inshore Fishing Communities -- 3. A Household Economy in the Modern Era -- 4. The Inshore Fishing Community: 'A Race Apart'? -- Part III. Female Agricultural Labourers -- 5. 'Muscular Femininity' -- 6. 'Clever hands' -- Household, Demographics and Autonomy.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Women -- Employment -- England, North East -- History; Wives -- Effect of husband's employment on -- England, North East -- History; Working class women -- England, North East -- History; Sexual division of labor -- England, North East -- History; Femmes mariées -- Effets du travail du mari sur -- Angleterre (Nord-Est) -- Histoire; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; HISTORY -- Europe -- Great Britain; Sexual division of labor; Wives -- Effect of husband's employment on; Women -- Employment; Working class women; England -- England, North East; Electronic books; History